FACTORES PERSONALES ASOCIADOS A LA ACTITUD HACIA EL PAPANICOLAOU EN MUJERES DE HUANCAYO, PERÚ EN EL AÑO 2025 - Sánchez Manrique, Alisson Molly (2025)
Introduction. Cervical cancer remains a preventable public health priority; however, screening gaps influence attitudes, particularly in provincial areas of Peru. Objectives. To determine the relationship between personal factors and attitudes toward Papanicolaou test among women in Huancayo. Methods. An observational, cross-sectional, and analytical study was conducted in Huancayo. A total of 216 sexually active women aged 18 years and older participated. A 29-item questionnaire was administered, comprising six sociodemographic and sexual behavior items, 13 knowledge-related items, and ten Likert-scale attitude items with five response options. Attitudes were categorized as positive, moderate, or negative; for inferential analysis, they were dichotomized into positive and moderate/negative. Adjusted prevalence ratios (aPR) and 95% confidence intervals (95%CI) were estimated. Results. Most participants were over 35 years old (68.5%). Attitudes were classified as positive (61.6%), moderate (24.1%), or negative (14.4%). Factors associated with a moderate/negative attitude included having moderate (aPR=4.13; 95%CI: 2.40–7.13; p<0.001) or low (aPR=6.78; 95%CI: 3.88–11.85; p<0.001) knowledge compared to high knowledge, having only basic education (aPR=2.30; 95%CI: 1.40–3.79; p=0.001) compared to university education, and identifying with a non-Catholic religion (aPR=0.48; 95%CI: 0.29–0.81; p=0.005) compared to no religious affiliation. No significant associations were found for age, marital status, number of sexual partners, or age at sexual initiation after adjustment. Conclusion. Educational level, knowledge about cervical cancer, and religious affiliation were significantly associated with moderate or negative attitudes toward cervical cancer screening among women in Huancayo.